The Poetics of Kinship - McKeon, Margaret; James, Kedrick (Art/Research International)

(untitled) (University of Alberta, 2024)
We write about the poetics of kinship with birds, trees, stones, and places as an act of resistance to neo-literal, neo-liberal destruction of refuge for non-human beings. Through research in which we situate ourselves in relation to the more-than-human, we take up kin as a verb. We offer experiences of kinning—that is, being present with that which is alive, has agency, and gives voice—as an invitation to readers to open themselves to listen in life and in research. We write in dialogue, through letters to each other, and we write poetically. With poetry’s attention to metaphor, embodiment, and vision, it is the natural language for describing the experience of kinning. Inquiring poetically helps us regain a communicative being-in-relation with wild, more-than-human others at a time of ecological distress, and to seek to better appreciate mystery and understandings that exceed human forms of knowing. Through this paper, we theorise from within our understandings and experiences about poetically kinning with the more-than-human.